2015
DOI: 10.3892/or.2015.4256
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by an ethanol extract of Poria cocos Wolf. in human leukemia U937 cells

Abstract: Poria cocos Wolf., which belongs to the Polyporaceae family, has been widely used as an Oriental traditional herbal medicine for centuries. Its sclerotium has been reported to possess a wide spectrum of pharmacological activities, including free-radical scavenging, anti-viral, anti-microbial, anti-inflammatory and anticancer activities. However, the cellular and molecular mechanisms of apoptosis induction by P. cocos in human cancer cells are poorly understood. In the present study, we investigated the pro-apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The concentration and time-dependent antiproliferative effect and pro-apoptotic effects of the examined extracts is related to the release of cytochrome C to the cytosol, activation of caspases − 3, − 8 and − 9, degradation of PARP and mitochondrial membrane potential loss. The obtained results indicate the potential of P. cocos in the treatment of leukemia [ 37 ]. A series of triterpenes with a similar inhibitory effect on the NF-κB signaling pathway has been isolated from another species, Inonotus obliquus [ 38 ].…”
Section: Resultsmentioning
confidence: 97%
“…The concentration and time-dependent antiproliferative effect and pro-apoptotic effects of the examined extracts is related to the release of cytochrome C to the cytosol, activation of caspases − 3, − 8 and − 9, degradation of PARP and mitochondrial membrane potential loss. The obtained results indicate the potential of P. cocos in the treatment of leukemia [ 37 ]. A series of triterpenes with a similar inhibitory effect on the NF-κB signaling pathway has been isolated from another species, Inonotus obliquus [ 38 ].…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies reported that ethanolic extracts of medicinal plants induce apoptosis via intrinsic and extrinsic pathways. The loss of mitochondrial membrane potential is a major characteristic of mitochondria-dependent apoptosis [ 39 , 40 ]. Hence, the analysis of mitochondrial cyt c release is an important measure of apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 family proteins involve pro-apoptotic and anti-apoptotic members. Bcl-2 proteins are vital mediators which control the mitochondrial pores to regulate cyt c release to aid in the apoptotic process [ 38 , 39 , 40 ]. The anti-apoptotic Bcl-2 proteins help in cell survival by inhibiting the pro-apoptotic proteins [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…66 It also has potential therapeutic effects for leukemia. 67 SGR has sedative and hypnotic effects, and it has obvious therapeutic value for restlessness, palpitations, and insomnia. SGR is mainly used in the treatment of depression in compounded preparations.…”
Section: Pharmacological Studies Of the Active Compounds Of Nine Chinmentioning
confidence: 99%